Effect of High-Frequency Repetitive Transcranial Magnetic Stimulation on Visual Selective Attention in Male Patients With Alcohol Use Disorder After the Acute Withdrawal - Feng, Zuxing; Wu, Qiao; Wu, Li; Zeng, Tingting; Yuan, Jing; Wang, Xin; Kang, Chuanyuan; Yang, Jianzhong (Frontiers in Psychiatry, 2022)
Objective: To investigate the effect of high-frequency repetitive transcranial magnetic stimulation(rTMS) on attention cue-reactivity in male patients with alcohol use disorder (AUD) after the acute withdrawal. Methods: A total of 90 male patients with AUD who were hospitalized were enrolled and divided into study and waiting groups by random number table. Eighteen patients dropped out during the study. After the alcohol withdrawal symptoms were eliminated, the study group received high-frequency rTMS at 10 Hz for 14 consecutive days, and the waiting group was administrated by sham rTMS. All subjects were evaluated for the attention cue-reactivity, impulsiveness, cognitive function by Oddball paradigm, Barratt Impulsiveness Scale version II (BIS-II), the Montreal Cognitive Assessment (MoCA) at baseline and after true or sham rTMS. Results: 1. There was no significant difference between the study and the waiting groups regarding drinking level, cognition level, and demographic data at baseline. 2. In the Oddball paradigm, both for alcohol-related and non-alcohol-related cues, the response times were significantly shorter in the study group after rTMS treatment than in the waiting-for-treatment group, either between the two groups or within the study group. There was no significant difference in accuracy rate for alcohol-related and non-alcohol-related cues between the two groups or within the study group after rTMS intervention. 3. The total score of MoCA was significantly increased, and the total score of BIS-II was significantly decreased in the study group after rTMS treatment, either between the two groups or within the study group. Conclusion: The results suggested that high-frequency rTMS could improve the attention bias of alcohol-related cues and impulsivity for AUD patients.